Açık ve laparoskopik kolesistektominin erken postoperatif dönem sıvı faz mide boşalmasına etkileri (ön çalışma) - BEKİROĞLU, GÜLNAZ NURAL (My University, 1996)
Today, laparoscopic cholecystectomy (LC) as a gold standard operation in the treatment of the gallbladder stones, has not been known enough how it does effect to earty postoperative period (EPP) liquid phase gastric emptying, comparing with the open cholecystectomy (OC). Gastric empyting scintigraphy (Tc 99m-DPTA) has been done to 12 laparoscopically, 6 conventionally treated cholecystectomy patients in prospective, randomized manner. Pre-operative, postoperative 1st and 7th day scintigraphic gastric empyting values (GEVs) were compared with each other. As compared with OC, decreasing GEV in LC at post-op 1st day 60.min was found to be increased at 7th day 0. and 30. min. significantly (p<0.05). However, both LC and OC groups GEVs were found to be statistically the similar levels at 7th day 60. min. We could not find a clinically reasonable difference between the effects of LC and OC on the liquid phase gastric empyting.

Günümüzde, safra kesesi taşlarının cerrahi tedavisinde altın standart ameliyat olan laparoskopik kolesistektominin (LK), erken postoperatif dönemde (EPD) mide boşalmasını nasıl etkilediği yeterince bilinmemektedir. Bu çalışmamızda, LK'nin EPD'de sıvı faz mide boşalmasını nasıl etkilediği açık kolesistektomi (AK) ile karşılaştırılarak incelenmiştir. LK yapılan 12, AK yapılan 6 hastaya prospektif, randomize olarak mide boşalım sintigrafisi (Tc 99m-DTPA) yapılmıştır. Pre-op, post-op 1. ve 7.gün ölçülen değerler birbirleri ile karşılaştırılmıştır. AK grubuna göre LK'de post-op, 1. gün 60.dk'da azalan mide boşalması, 7.gün 0. ve 30.dk'larda AK'den istatistiksel olarak daha yüksek olmuştur. Her iki grubun boşalmaları 7.gün 60.dk'da istatistiksel olarak aynı düzeylerde bulunmuştur. Sonuç olarak LK ve AK arasında sıvı faz mide boşalmaları açısından klinik olarak önemli sayılabilecek bir fark olmadığı düşünülmüştür.
He effects of open and laparoscopic cholecystectomies on early postoperative period liquid phase gastric emptying (preliminary study)
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Surgery Medicine Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; TIBBİ BİLİŞİM; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; MEDICAL INFORMATICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Cerrahi; Dahiliye; Tıbbi Bilişim; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Surgery; Internal Medicine; Health Informatics; Family Practice; Medicine (miscellaneous); General Medicine; LAPAROSKOPİK KOLESİSTEKTOMİ; AÇIK KOLESİSTEKTOMİ; MİDE BOŞALMASI; LAPAROSCOPIC CHOLECYSTECTOMY; OPEN CHOLECYSTECTOMY; GASTRIC EMPYTING